A multiple criteria decision support system for analyzing the correlation between the thickness of a thermo-insulation layer and its payback period of the external wall - Aviža, Donatas; Turskis, Zenonas; Kaklauskas, Artūras (Journal of Civil Engineering and Management, 2015)
A case study provides the correlation analysis of the thickness of the thermo-insulation layer (expanded polystyrene – EPS70) of the typical details of the external wall and energy performance class in a modern newly constructed residential low-energy building (one and two-room apartment). The conducted analysis focused on what impact different geographical areas of building construction and different energy performance classes of the building may had on the thickness of the thermo-insulation layer. Lithuania was chosen as the object of this study. Calculations were carried out in seven towns, including Vilnius, Klaipeda, Kaunas, Siauliai, Panevezys, Utena and Dukstas. According to requirements for legal acts passed in the Republic of Lithuania and to Directive 2010/31/EU (2010), as a result, the necessary thickness of thermo-insulation layers (EPS70) and a payback period were calculated. A multiple criteria decision support system for analyzing the correlation between the thickness of the thermo-insulation layer and its payback period of the external wall (DSS-ACTILPW) consisting of a database, a database management system, a model-base, a model-base management system and a user interface was developed. Information on the performed analysis is important to building designers, energy consumption auditors and investment experts who make the final decisions on energy efficiency of buildings in the residential building sector.